Interfacial Activity of Amine‐Functionalized Polyhedral Oligomeric Silsesquioxanes (POSS): A Simple Strategy To Structure Liquids. (24th June 2019) - Hou, Honghao; Li, Jin; Li, Xiangming; Forth, Joe; Yin, Jie; Jiang, Xuesong; Helms, Brett A.; Russell, Thomas P.
Abstract: Amine‐functionalized polyhedral oligomeric silsesquioxane (POSS), the smallest, monodisperse cage‐shaped silica cubic nanoparticle, is exceptionally interfacially active and can form assemblies that jam the toluene/water interface, locking in non‐equilibrium shapes of one liquid phase in another. The packing density of the amine‐functionalized POSS assembly at the water/toluene interface can be tuned by varying the concentration, the pH value, and the degree of POSS functionalization. Functionalized POSS gives a higher interface coverage, and hence a lower interfacial tension, than nanoparticle surfactants formed by interactions between functionalized nanoparticles and polymeric ligands. Hydrogen‐bonded POSS surfactants are more stable at the interface, offering some unique advantages for generating Pickering emulsions over typical micron‐sized colloidal particles and ligand‐stabilized nanoparticle surfactants. Abstract : Tenside auf Basis ligandenfreier POSS‐Nanopartikel organisieren sich an einer Flüssig‐flüssig‐Grenzfläche. Sie ermöglichen die Herstellung von Pickering‐Emulsionen und strukturierten Flüssigkeiten und ergänzen so Verfahren, die auf der Verwendung kolloider Mikropartikel und ligandenstabilisierter Nanopartikel‐Tenside basieren.